ASAS PERTANGGUNGJAWABAN TERHADAP KORPORASI YANG MELAKUKAN TINDAK PIDANA PERBANKAN - Nurul Sasmita (Program Magister Hukum Universitas Lambung Mangkurat, 2016)
The aims of this thesis is (1) to investigate andexplain the positions of corporations in conducting banking criminalacts, and (2) also to identify and explain the criminal responsibility ofbank as the perpetrator in banking criminal acts. This research isnormative, conceptual approach and the approach of legislationregarding responsibility principles of the corporation for banking criminalacts.Corporations have chances in committing a crime, especially bankingcriminal acts just by making a corporation recognized as a subject ofexistence apart from human beings, so that in practice there is a criminal offense committed by the corporation. The corporation takespart in the occurrence of a crime. In practice, the determination of acriminal offenseconducted by the corporation is known through two things: first, the works of the committee: they should be constructed as theyuse the principles of the liability of corporation’s criminal actions. Principally, stakeholders and officials or employees of a corporationhave the responsibility for its owncorporate actions; second, errors in the corporation,as long as it is in the science of criminal law, the overview of criminals is still oftenassociated with physical actions performed by the manufacturers(fysieke dader) but this can be overcome by the study of